GeV-scale electron acceleration in a gas-filled capillary discharge waveguide - Karsch, S; Osterhoff, J; Popp, A; Rowlands-Rees, T; Major, Z; Fuchs, M; Marx, B; Hörlein, R; Schmid, K; Veisz, L; Becker, S; Schramm, U; et al. (Institute of Physics Publishing Ltd., 2007)
We report experimental results on laser-driven electron acceleration with low divergence. The electron beam was generated by focussing 750mJ, 42 fs laser pulses into a gas-filled capillary discharge waveguide at electron densities in the range between 10^18 and 10^19 cm^-3. Quasi-monoenergetic electron bunches with energies as high as 500 MeV have been detected, with features reaching up to 1 GeV, albeit with large shot-to-shot fluctuations. A more stable regime with higher bunch charge (20-45 pC) and less energy (200-300 MeV) could also be observed. The beam divergence and the pointing stability are around or below 1 mrad and 8 mrad, respectively. These findings are consistent with self-injection of electrons into a breaking plasma wave.